Energetic valorization of waste tires - Machin, Einara Blanco [UNESP]; Pedroso, Daniel Travieso [UNESP]; Carvalho, Joao Andrade de [UNESP] (Elsevier B.V., 2017)
Significant high levels of available waste tires in Brazil, which reached approximately 473 thousand tons in 2015, offer an attractive potential for their use as fuel in advanced thermal conversion processes. Technologies for energetic valorization of waste tires were reviewed and two alternatives based on updraft gasification in a modified reactor design were proposed. First of all, a large-scale updraft gasifier on IGCC (Integrated Gasification Combined Cycle) was considered for the gasification of the derived fuel from waste tires, capable to produce between 10.8 and 16.1 MJ of electric energy per kg of derived fuel from waste tires fed to the reactor. The second alternative considered a small-scale updraft gasifier feeding an internal combustion engine, coupled to an electricity generator for the production of up to 8.2 MJ of electric energy per kg of derived fuel from waste tires fed to the reactor. Implementation of these technologies will allow energetic valorization of waste tires in Brazil, solving their disposal problems, creating jobs, reducing negative disposal environmental impacts in landfills, and increasing distributed generation of electricity.
Keywords: Updraft; Gasification; Waste tires; Cogeneration; Energetic valorization